Art as therapy in virtual reality: A scoping review - Hadjipanayi, Christos; Banakou, Domna; Michael-Grigoriou, Despina (Frontiers in Virtual Reality, 2023)
This scoping review focuses on therapeutic interventions, which involve the creation of artworks in virtual reality. The purpose of this research is to survey possible directions that traditional practices of art therapy and therapeutic artmaking could take in the age of new media, with emphasis on fully immersive virtual reality. After the collection of papers from online databases, data from the included papers were extracted and analyzed using thematic analysis. The results reveal that virtual reality introduces novel opportunities for artistic expression, self-improvement, and motivation for psychotherapy and neurorehabilitation. Evidence that artmaking in virtual reality could be highly beneficial in therapeutic settings can be found in many aspects of virtual reality, such as its virtuality, ludicity, telepresence capacity, controlled environments, utility of user data, and popularity with digital natives. However, deficiencies in digital literacy, technical limitations of the current virtual reality devices, the lack of tactility in virtual environments, difficulties in the maintenance of the technology, interdisciplinary concerns, as well as aspects of inclusivity should be taken into consideration by therapy practitioners, researchers, and software developers alike. Finally, the reported results reveal implications for future practice.